Radiation Dose Calculation Analysis During The Dismantling of Disused Sealed Radioactive Sources at CNESTEN: MCNP Code Simulation Results - El Azzaoui, B.; Kabach, O.; Outayad, R.; Messous, M. Y.; Bergaoui, K.; Nbaoui, K.; Kadiri, J.; Chakir, E.; Alibrahmi, E.; Kharchaf, A. (National Research and Innovation Agency, 2024)
Disused Sealed Radioactive Sources (DSRS) present significant risks of radiation exposure and environmental contamination during dismantling. Despite their sealed nature, DSRS can emit ionizing radiation, necessitating careful management to mitigate health risks. This article presents the MCNP simulation results of dosimetric operational quantities, namely Hp(3), Hp(10), and H(0.07), for hands and feet. This study focuses on a 60Co source, due to its high radiation energy levels and widespread use in various socioeconomic sectors. The assessment of radiation exposure levels enabled the improvement of occupational radiation protection measures related to critical areas and steps in the dismantling process. According to the obtained results with the 60Co source at its initial activity, and considering the maximum task duration, the dismantling process contributes to approximately 72.35 % of the daily dose limit of 80 µSv for worker category A, for the whole body. Therefore, these findings can contribute to a better understanding of radiation exposure risks and confirm compliance with regulatory requirements.